VIDEO DESIGN INTRODUCTION OF TOURIST ATTRACTION ON KALOK ISLAND WITH A CINEMATIC APPROACH - Jimmy Pratama; Sutarto Wasatan (Universitas Internasional Batam, 2022)
Batam City is one of the cities that has become a tourist destination for local and foreign tourists, located in the Riau Islands Regency, Riau Islands Regency, there are many islands and are not widely known to the public due to lack of information dissemination, one of which is Kalok Island. In this study, we will examine the design of a tourist attraction introduction video with a cinematic approach, where the video is made with a conceptualized plot and uses the Multimedia Development Life Cycle (MDLC) method. will be made, the design stage, carried out in detail and in detail, the stage of collecting materials, preparing the materials needed when shooting, the manufacturing stage, where the project will be designed, the testing stage, testing whether it is as planned, the distribution stage, where the video has been completed and published on the YouTube platform. In order to introduce Tourism Objects on Kalok Island, the researchers made a video with a cinematic approach so that the video can be used as an effective medium of information to introduce to the wider community about the existence of Kalok Island and can increase the interest of tourists to visit the island